1993
DOI: 10.1677/jme.0.0110231
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of insulin-like growth factor-I receptor mRNA in rat brain. Regulation in the hypothalamo-neurohypophysial system

Abstract: The distribution and regulation of mRNA for the IGF-I receptor (IGF-I-R) in the adult rat brain were studied by in-situ hybridization with a 35S-labelled cRNA probe. The pituitary gland showed a strong hybridization signal in the pars tuberalis (the surface of the median eminence), pars distalis and pars intermedia. Within the brain, a strong hybridization signal was found in the circumventricular organs, olfactory bulb, hippocampus, cerebellum and hypothalamus. IGF-I-R mRNA was consistently found in cell bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…Consequently, the adolescent hypersensitivity to estradiol negative feedback suppression of LH secretion may be the result of an increased GABAergic inhibition of glutamate receptor excitation of LHRH neurons. Although the specific hypothalamic distribution of IGF-I receptors has yet to be described in primates, IGF-I receptors in rats are found in the median eminence (Lesniak et al 1988, Werther et al 1989, Aguado et al 1993 and IGF-I receptor mRNA in this region increases prior to first proestrus in rats (Hiney et al 1996). Co-localization and functional analysis studies of neurons containing IGF-I receptors and those immunoreactive for GABA and/or glutamate may help determine whether IGF-I diminishes estradiol-induced activation of GABAergic inhibition of glutamate neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the adolescent hypersensitivity to estradiol negative feedback suppression of LH secretion may be the result of an increased GABAergic inhibition of glutamate receptor excitation of LHRH neurons. Although the specific hypothalamic distribution of IGF-I receptors has yet to be described in primates, IGF-I receptors in rats are found in the median eminence (Lesniak et al 1988, Werther et al 1989, Aguado et al 1993 and IGF-I receptor mRNA in this region increases prior to first proestrus in rats (Hiney et al 1996). Co-localization and functional analysis studies of neurons containing IGF-I receptors and those immunoreactive for GABA and/or glutamate may help determine whether IGF-I diminishes estradiol-induced activation of GABAergic inhibition of glutamate neurons.…”
Section: Discussionmentioning
confidence: 99%
“…While such effects have yet to be demonstrated, several studies indicate that many of the components of the IGF system are present in the adult MNS. For example, IGF-I immunoreactivity has been detected in magnocellular neurons of the paraventricular, supraoptic and accessory nuclei following colchicine treatment [ 19], and these neurons have also been reported to express IGF-I receptor mRNA [20]. The presence of high-affinity binding sites for [125I]IGF-I in the MNS sug gests that functional receptors are present [21], If IGF-I does act in an autocrine/paracrinc manner in mature magnocellular neurons, production of IGFBP-2 by pitui cytes may be analogous to synthesis of the binding protein by astrocytes in the developing retina and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoreactive rat LH (IR-LH) FSH (IR-FSH) and GH (IR-GH) were measured by the National Hormone and Pituitary Program/NIDDK (Bethesda, Md, USA) kits. IGF-I was separated from its binding proteins by acid extraction and reverse-phase column chromatography procedure using Sep-Pack C18 cartridges (Waters Millipore, Milford, Mass., USA) [6]and assayed by a commercial IGF-I radioimmunoassay (RIA) kit (Nichols, San Juan Capistano, Calif., USA).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown [4]that IGF-I of peripheral origin contributes to the initiation of female puberty by stimulating GnRH release from the hypothalamus. We and others have reported that IGF-I and its receptor are expressed in the hypothalamus and median eminence (ME) [5, 6, 7]. Therefore, centrally located IGF-I may regulate GnRH through autocrine, paracrine or endocrine functions within the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%